Processing of chicken stomachs using ultrasonics - Strashynskyi, Igor; Pasichnyi, Vasyl; Shingelskij, M.; Kosiuk, Olha (My University, 2023)
The environmentally friendly technological method of softening chicken gizzards by sonication is effective in improving the quality of meat products, including including the technology of which involves the use of sauces. Екологічно чистий технологічний спосіб розм’якшення курячих шлунків методом обробки ультразвуком є ​​ефективним для підвищення якості м’ясних продуктів, у тому числі технологія якого передбачає використання соусів.
Keywords: кафедра технології м’яса і м’ясних продуктів; шлунок курячий; chicken stomach; ultrasound; ультразвук